The role of radiation therapy in locally advanced and metastatic renal cancer - Fijuth, Jacek (Contemporary Oncology/Współczesna Onkologia, 2005)
Adjuvant radiotherapy (RT) in locally advanced renal cell carcinoma is not a standard treatment. Preoperative RT can be considered in nonmetastatic, unresectable tumours. This strategy can improve further respectability of locally advanced tumours. Recommended total dose of preoperative RT is 45 Gy in 1,8- to 2-Gy fractions. Postoperative RT can be considered in case of high risk of local recurrence, micro- and macroscopic nonradical resection, infiltration of perinephric fat extension, adrenal invasion (T3a or T3c). In case of paraaortic lymph-node involvement the risk of distant metastatic spread is high and postoperative RT does not influence the overall survival. Involvement of the renal vein and inferior vena cava does not necessarily increase the risk of local recurrence and should not be considered an indication for RT. The treatment planning should be done in 3D and 3D-CRT should be applied. Recommended total dose is 45-50 Gy in 1,8- to 2-Gy fractions to the nephrectomy bed and regional lymph nodes with a boost to small volumes of microscopic or gross residual disease with an additional 10 to 15 Gy. Patients with limited metastatic disease with good performance status have possibility of long survival and aggressive treatment for palliation should be considered. Treatment fields should encompass metastatic foci with 2- to 3-cm margins. RT doses of 35 to 40 Gy provide symptomatic relief in 64% to 845 of patients treated.